Evaluation of blended fertilizer rates for improving production of food barley (Hordeum vulgare L.) in Semen Ari District, Southwestern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Depletion of soil fertility, depletion of macro- and micro-nutrients and soil organic matter and inappropriate and imbalanced fertilizer application are among the most important factors that reduces the food barley production in Ethiopia. Therefore, the experiment was conducted to evaluate NPSB blended fertilizer rate effect on improving production of food barley in Semen Ari District, Southwestern Ethiopia during main cropping season. Control, (142 NPS + 159 Urea) kg ha-1, (150 NPSB + 41 Urea) kg ha-1, (200 NPSB + 72 Urea) kg ha-1, (250 NPSB + 102 Urea) kg ha-1 and (100 NPSB + 161 Urea) kg ha-1 treatments were used for the experiment which laid out in RCBD following three replication with spacing of 20 cm between rows; and HB 1307 improved food barley seeds were drilled on prepared rows. Full dose of blended and potassium fertilizers were applied at planting time and urea was applied in two split. The result revealed that food barley responded well to application of N, P, S and B than the unfertilized one. Application of 100 kg ha-1 NPSB + 161 kg ha-1 Urea resulted in highest grain yield of 3806.3 kg ha-1, while the lowest grain yield of 1939.2 kg ha-1 was recorded from the nil. Moreover, the highest net benefit of 32124.56 ETB ha-1 and economic returns of 942.2% was recorded in response to application of 100 kg ha-1 NPSB + 161 kg ha-1 Urea. Application of 100 kg ha-1 NPSB + 161 kg ha-1 Urea gave 49.05% yield increment and 40.24% increment in economic return over the control. Therefore, we recommend application of 100 kg ha-1 NPSB + 161 kg ha-1 Urea for farmers and investor’s in study area and similar agro-ecologies as it was optimum for improving food barley production. Further studies and investigation should be done on plant nutrient uptake, nutrient use efficiency and over location.Int. J. Agril. Res. Innov. Tech. 11(2): 10-17, Dec 2021